2023
DOI: 10.1038/s41598-023-28467-6
|View full text |Cite
|
Sign up to set email alerts
|

Variability of trunk muscle synergies underlying the multidirectional movements and stability trunk motor tasks in healthy individuals

Abstract: Muscle synergy analysis is useful for investigating trunk coordination patterns based on the assumption that the central nervous system reduces the dimensionality of muscle activation to simplify movement. This study aimed to quantify the variability in trunk muscle synergy during various trunk motor tasks in healthy participants to provide reference data for evaluating trunk control strategies in patients and athletes. Sixteen healthy individuals performed 11 trunk movement and stability tasks with electromyo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Theses trunk muscles present bilateral and unilateral connectivity defined by the anatomical constraints (e.g., common origin and insertion of muscles) and the neural circuitry that projects to functional groups of muscles for dynamic motor control [ 11 ]. Therefore, assessing multiple patterns of trunk EMG activity in an integrative fashion is required to accurately identify the overall picture of altered motor control in CLBP [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Theses trunk muscles present bilateral and unilateral connectivity defined by the anatomical constraints (e.g., common origin and insertion of muscles) and the neural circuitry that projects to functional groups of muscles for dynamic motor control [ 11 ]. Therefore, assessing multiple patterns of trunk EMG activity in an integrative fashion is required to accurately identify the overall picture of altered motor control in CLBP [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…NMF employs linear extraction and separates EMG matrices into time-invariant weighted activations of a group of muscles (muscle weighting components) and time-variant activation profiles (temporal pattern components) [ 16 , 18 , 19 ]. For this method, large-scale and high-dimensional EMG data recorded during a variety of motor tasks are essential, as muscle synergies are the fundamental building blocks of neural constraints [ 20 ]; thus, it may address the question of how the CNS adapts in the presence of CLBP [ 12 ]. Furthermore, incorporating many trunk motor tasks is beneficial, as this increases the possibility of revealing the motor control strategies in CLBP that may have altered trunk motor control during different motor tasks [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the local minima inherent in NMF, each synergy extraction was repeated 300 times, and the VAF was calculated at each iteration. The iterations with the highest VAF were maintained (Saito et al, 2021(Saito et al, , 2022(Saito et al, , 2023Yokoyama et al, 2016Yokoyama et al, , 2021. VAFs >0.90% were used to identify the optimal number of synergies commonly used in the literature (Saito et al, 2021(Saito et al, , 2022(Saito et al, , 2023Yokoyama et al, 2016Yokoyama et al, , 2021.…”
Section: Muscle Synergy Extractionmentioning
confidence: 99%
“…The iterations with the highest VAF were maintained (Saito et al, 2021(Saito et al, , 2022(Saito et al, , 2023Yokoyama et al, 2016Yokoyama et al, , 2021. VAFs >0.90% were used to identify the optimal number of synergies commonly used in the literature (Saito et al, 2021(Saito et al, , 2022(Saito et al, , 2023Yokoyama et al, 2016Yokoyama et al, , 2021. It was suggested that the criterion VAF >0.90% ensures a sufficient representation of the data (Turpin et al, 2021), although this is still debated (Barradas et al, 2020).…”
Section: Muscle Synergy Extractionmentioning
confidence: 99%